2014
DOI: 10.1002/jor.22748
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent PTH administration and mechanical loading are anabolic for periprosthetic cancellous bone

Abstract: The purpose of this study was to determine the individual and combined effects on periprosthetic cancellous bone of intermittent PTH (iPTH) and mechanical loading at the cellular, molecular, and tissue levels. Porous titanium implants were inserted bilaterally on the cancellous bone of adult rabbits beneath a loading device attached to the distal lateral femur. The left femur received a sham loading device. The right femur was loaded daily, and half of the rabbits received daily PTH. Periprosthetic bone was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 54 publications
3
24
1
Order By: Relevance
“…A third possibility would be that risedronate had a negative effect, which appears unlikely, as bisphosphonates have been shown not to impair healing in comparison with placebo [36][37][38] , with the potential exception of distal radial fractures 39 , and likely improve implant fixation 40 . A positive effect of teriparatide on human fracture recovery would not be surprising, considering the positive effect on bone-healing in various animal models [13][14][15][16]21,41 .…”
Section: Discussionmentioning
confidence: 99%
“…A third possibility would be that risedronate had a negative effect, which appears unlikely, as bisphosphonates have been shown not to impair healing in comparison with placebo [36][37][38] , with the potential exception of distal radial fractures 39 , and likely improve implant fixation 40 . A positive effect of teriparatide on human fracture recovery would not be surprising, considering the positive effect on bone-healing in various animal models [13][14][15][16]21,41 .…”
Section: Discussionmentioning
confidence: 99%
“…Although preclinical studies using PTH in animal models are promising (60)(61)(62)(63)(64)(65) and proof-of-concept clinical trials (66,67) and sporadic case reports in humans (68,69) showed an anecdotal benefit of teriparatide in various fractures, to date there are no well-controlled clinical trials to support the hypothesis that teriparatide improves fracture healing. Huang and colleagues (70) have recently reported that 6 months of teriparatide was associated with faster fracture healing, better quality of life, and lower frequency of lag screw cutout and mortality rates in 189 patients with intertrochanteric fractures.…”
Section: Discussionmentioning
confidence: 99%
“…21-24 However, continuous dosing results in increased osteoclast activation and lifespan, and thus enhanced endosteal resorption. In contrast, intermittent dosing results in increased trabecular bone volume.…”
Section: Anabolic Role Of Pthmentioning
confidence: 99%